Identification of microRNAs associated with abdominal aortic aneurysms and peripheral arterial disease. Issue 7 (2nd April 2015) - Stather, P. W.; Sylvius, N.; Sidloff, D. A.; Dattani, N.; Verissimo, A.; Wild, J. B.; Butt, H. Z.; Choke, E.; Sayers, R. D.; Bown, M. J.
Abstract Background MicroRNAs are crucial in the regulation of cardiovascular disease and represent potential therapeutic targets to decrease abdominal aortic aneurysm (AAA) expansion. The aim of this study was to identify circulating microRNAs associated with AAA. Methods Some 754 microRNAs in whole‐blood samples from 15 men with an AAA and ten control subjects were quantified using quantitative reverse transcriptase–PCR. MicroRNAs demonstrating a significant association with AAA were validated in peripheral blood and plasma samples of men in the following groups (40 in each): healthy controls, controls with peripheral arterial disease (PAD), men with a small AAA (30–54 mm), those with a large AAA (over 54 mm), and those following AAA repair. MicroRNA expression was also assessed in aortic tissue. Results Twenty‐nine differentially expressed microRNAs were identified in the discovery study. Validation study revealed that let‐7e (fold change (FC) –1·80; P = 0·001), miR‐15a (FC −2·24; P < 0·001) and miR‐196b (FC −2·26; P < 0·001) were downregulated in peripheral blood from patients with an AAA, and miR‐411 was upregulated (FC 5·90; P = 0·001). miR‐196b was also downregulated in plasma from the same individuals (FC −3·75; P = 0·029). The same miRNAs were similarly expressed differentially in patients with PAD compared with healthy controls. Validated and predicted microRNA targets identified through miRWalk revealed that these miRNAs were all regulators of AAA‐related genes (vascular cell adhesion molecule 1, intercellular cell adhesion molecule 1, DAB2 interacting protein, α1‐antitrypsin, C‐reactive protein, interleukin 6, osteoprotegerin, methylenetetrahydrofolate reductase, tumour necrosis factor α). Conclusion In this study, circulating levels of let‐7e, miR‐15a, miR‐196b and miR‐411 were differentially expressed in men with an AAA compared with healthy controls, but also differentially expressed in men with PAD. Modulation of these miRNAs and their target genes may represent a new therapeutic pathway to affect the progression of AAA and atherosclerosis.